Evaluating the Nature and Extent of Burglary at Residential Premises in Namakgale Policing Area, South Africa - Mundlovu, M.; Khosa, D.; Zenzile, E. (International Journal of Criminology and Sociology, 2021)
The main objective of this paper was to explore the nature and extent of burglary at residential grounds in the Namakgale policing area, after realisation of higher manifestations and uncontrollable nature of this crime. This paper utilised a qualitative research approach, supported by the phenomenological research design. Altogether, 30 participants were purposively selected from diverse target groups, which consists of the South African Police Service Detectives, uniform police officers, Community Policing Forum (CPF) members and managers, Community Leaders and Faith-based organisation leaders, and local community members. The objectives of the paper were realised by the use of one-on-one semi-structured interviews for data collection, and thematic analysis, in order to analyse the gathered data. Research findings of this paper revealed that the current strategies of traditional policing, such as a) foot patrolling offered by the selected stakeholders, and b) the vehicle patrolling rendered by the local SAPS members, are deemed to be ineffective. There is an increase in the number of burglaries at residential premises at Namakgale policing area, and the reported cases tend to be often unsolved. There are constant complaints made by community members about burglary in their premises. It is also established that security systems can play an essential role in deterring the commission of this crime and the failing trust within the community members and the local SAPS should be rebuilding. This empirical research paper recommends that Namakgale community, local SAPS and other relevant stakeholders should clearly understand the Modus Operandi (MO) used in the commission of this ordeal crime. The understanding of the MO would serve as a detail-rich information and subsequently influence strategies, on how to effectively respond to this crime.